Charge‐Accumulating‐Flutter‐Based Triboelectric Nanogenerator via Discharge Gateway. Issue 14 (19th February 2023) - Heo, Deokjae; Son, Jin‐ho; Kim, Dongchang; Song, Myunghwan; Ryu, Hanwook; Kim, Sunghan; Choi, Kyungwho; Lin, Zong‐Hong; Kim, Dongseob; Hong, Jinkee; Lee, Sangmin
Abstract: For triboelectric nanogenerators (TENGs), achieving both high root‐mean‐square (RMS) current output and portability remains a challenge. Here, a charge‐accumulating‐flutter‐based triboelectric nanogenerator (CAF‐TENG) with ultrahigh RMS current and average power density/portability is proposed. Because of the electron accumulation/discharge mechanism and electrical/mechanical flutter device design, the CAF‐TENG can generate an RMS voltage, RMS current, and average power density of 44 V, 36 mA, and 26 mW cm −3, respectively. The CAF‐TENG is optimized via quantitative electrical/mechanical analysis. CAF‐TENG can power an array of 2000 commercial LEDs continuously and charge high‐capacitance capacitors/commercial lithium batteries. Furthermore, as a practical application, a mask‐valve‐integrated CAF‐TENG is fabricated, which can power eight commercial lamps (5 W) continuously and operate a commercial Bluetooth tracker by charging a capacitor in a daily respiration scenario. Abstract : The charge‐accumulating‐flutter‐based triboelectric nanogenerator (CAF‐TENG) exhibits an outstanding output performance and portability owing to the proposed charge accumulation‐discharge mechanism and mechanical design/compact size. Furthermore, a mask‐valve‐integrated CAF‐TENG can power eight commercial lamps (rated power of one lamp: 5 W) and operate a Bluetooth tracker in a daily respiration scenario.